FUTURE ENGINEERS IN A DIGITAL EDUCATIONAL ENVIRONMENT PROFESSIONAL IMPROVING COMPETENCES - Eshpulatova Husniya (Bright Mind Publishing, 2026)
This article outlines the tasks of forming and improving the professional competencies of future engineers in a digital educational environment in Uzbekistan and improving the professional competencies of engineers in a digital educational environment in technical higher educational institutions.
Keywords: Digital education, professional competence, competence, modular training.